2015
DOI: 10.1186/s12885-015-1487-3
|View full text |Cite
|
Sign up to set email alerts
|

PIpelle Prospective ENDOmetrial carcinoma (PIPENDO) study, pre-operative recognition of high risk endometrial carcinoma: a multicentre prospective cohort study

Abstract: BackgroundEndometrial carcinoma is the most common gynaecologic malignancy in industrialised countries and the incidence is still rising. Primary treatment is based on preoperative risk classification and consists in most cases of hysterectomy with bilateral salpingo-oophorectomy. In patients with serous and clear cell histology a complete surgical staging is mandatory. However, in routine clinical practice final histology regularly does not correspond with the preoperative histological diagnosis. This results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“… 14 However, the final diagnosis of these cases following hysterectomy was endometrial cancer. 15 The Pipelle may have diagnostic pitfalls in EAPs such as in our case. One report revealed that the sensitivity of Pipelle and curettage was 93.8% and 97%, respectively, in patients with low-grade cancer, and 99.2% and 100%, respectively, in patients with high-grade cancer.…”
Section: Discussionmentioning
confidence: 68%
“… 14 However, the final diagnosis of these cases following hysterectomy was endometrial cancer. 15 The Pipelle may have diagnostic pitfalls in EAPs such as in our case. One report revealed that the sensitivity of Pipelle and curettage was 93.8% and 97%, respectively, in patients with low-grade cancer, and 99.2% and 100%, respectively, in patients with high-grade cancer.…”
Section: Discussionmentioning
confidence: 68%
“…This may require confirmation of a similar correlation between serum L1CAM expression and positive lymph node metastases in EC patients, or feasibility of preoperative expression levels in endometrial biopsies. The results of the currently ongoing Pipelle Prospective endometrial carcinoma (PIPENDO) study which includes preoperative and postoperative L1CAM expression analyses, will thus be eagerly awaited [24]. Secondly, increased expression in advanced, high-risk ECs of this transmembrane protein may offer potential novel therapeutic strategies to target the extracellular portion of L1CAM in EC patients, and simultaneously allow for biomarker selection of these patients by IHC.…”
Section: Discussionmentioning
confidence: 99%
“…Performance was validated using 2 prospective multicenter external data sets: the Molecular Markers in Treatment in Endometrial Cancer (MoMaTEC) cohort (n = 446), including patients treated between May 2001 and 2010, and the PIpelle Prospective ENDOmetrial carcinoma (PIPENDO) cohort (n = 384), including patients treated between September 2011 and December 2013 [8,22]. Patients from these cohorts were only included if they had a minimal subset of variables: preoperative tumor grade, at least 3 molecular biomarkers, at least one of the clinical preoperative markers, and information on outcome.…”
Section: Bn Validationmentioning
confidence: 99%